Risk Factors of Stunting Among Under-Five Children in the Babirik Subdistrict, Hulu Sungai Utara Regency - Hamidah Hamidah; Niken Widyastuti Hariati; Rahmani Rahmani; Siti Mas'Odah (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Stunting is a chronic nutritional problem in toddlers in Indonesia, including in Babirik District, Hulu Sungai Utara Regency, with a prevalence rate of 23.98%, which impacts children's growth and development. This study aimed to analyze the risk factors for stunting in toddlers aged 12–59 months in Babirik District. This study used an observational analytical design with a case-control approach in 108 toddlers with a 1:1 ratio. The variables studied included maternal age during pregnancy, maternal nutritional status during pregnancy, maternal history of pregnancy complications, birth weight, history of exclusive breastfeeding, and history of complementary feeding. Data were collected through questionnaires and interviews with searches of KIA books and medical records, data were analyzed using the Chi-square test and odds ratio (OR). The results showed that the majority of mothers during pregnancy were 20–35 years old (83.3%), with normal nutritional status (65.7%), and did not experience pregnancy complications (75.9%). Most toddlers were born with normal weight (88%), received exclusive breastfeeding (54.6%), and received complementary foods on time (57.4%). Maternal nutritional status during pregnancy (p-value = 0.008), birth weight (p-value = 0.008; OR = 1.895), and exclusive breastfeeding (p-value = 0.001; OR = 1.317) were significantly associated with stunting, while maternal age, pregnancy complications, and appropriate complementary feeding were not associated (p-value > 0.05). It is recommended that stuntingprevention efforts focus on improving maternal nutritional status during pregnancy, monitoring birth weight, and strengthening exclusive breastfeeding through health services